Em nome das redes: família, amizades políticas e alianças em Sergipe - Santos, Pâmella Synthia Santana (2020)
This dissertation analyzed the relation between professional politics, family resources, and political groupings with the case of state and federal deputies who were elected in 2014 and 2018 in the Sergipe state. Not only was the question of a specific resource as a legitimator brought to discussion, but also a collaborative that enables the insertion and success in professional politics through family-based networks. Thus, the specific goals revolved around a) analyzing the social history of family groupings in politics in Sergipe to understand the political dynamics; b) to examine the conditions that allow these groups and families to perpetuate themselves in politics; c) to analyze how the networks between the groups of the state countryside were formed and found; d) to understand the state parties configuration according to the relations networks; e) to analyze the changes experienced in the countryside municipalities through the party impact; f) to understand the incorporation of political heritage through marriage or sponsorship; finally, g) to identify elements that made possible the development of the political career of the actors in question. The methodological elements consisted of: complete survey of information through CPDOC, Assembly websites, Chamber, Senate, personal websites, etc.; deepening study of families of these actors through the social history of family politics issue in Sergipe; and reading the data related to political recompositions in the state through TRE-SE and TSE1 ; In this way, this dissertation is divided into four chapters: the first addressed the theoretical orientations about the conceptualizations of "family", "groupings" and "professional politics"; the second chapter searched aimed to make a socio-historical rescue of politics groups in Sergipe from the oligarchies until the 2010s; the third chapter analyzed the political-party representativeness in the 8 Sergipe territories; finally, the fourth chapter discussed the logic and patterns of recruitment, how the family resource is mobilized by the actors in favor of family-based groups and networks and how this allows the construction of a political-professional self. The thesis of this research shows the logic of grouping and parties must be taken into account, then, in the Sergipe’s case, the concentration of parties in certain groups is a crucial strategy for the networks' maintenance, thus starting from the city level to the state level. In addition, when recruiting from within the groups themselves, dependency and party loyalty is greater, which gives less autonomy, or reduced freedom in the choice of different opportunities, for the parliamentarian to direct his career. Therefore, this reduced autonomy ends up becoming a guaranteed support, since the feeling of adhesion and belonging is still a characteristic of the groups, mainly in the municipalities. When done in a reverse way, it runs the risk of destabilizing the group's structure and hence not contributing to its maintenance in political power. This only reaffirms that the policy made within this dynamic cannot be calculated by the actors, but strategies must be constructed to glimpse these eventualities, always considering the benefits and harms inserting someone who does not come from the networks already built. In this way, it was possible to identify the political recomposition of Sergipe that has been detaching itself from the image of old traditional families and building a kind of “new-old family-based networks” with new actors, but with renewed groups that previously did not have so much state highlight.